SOLID DISPERSION TABLETS IN IMPROVING ORAL BIOAVAILABILITY OF POORLY SOLUBLE DRUGS - SARKAR, PRASENJIT; DAS, SAUMYAJYOTI; MAJEE, SUTAPA BISWAS (International Journal of Current Pharmaceutical Research, 2022)
Recent advances in the field of conversion of solid dispersions of poorly water-soluble drugs in a wide range of hydrophilic or water-soluble carriers into solid dispersion tablets have shown great promise in improving solubility, dissolution rate and oral bioavailability of such drugs. Moreover, proper choice of tablet excipients during tableting of optimised solid dispersions can produce either fast/rapid or sustained drug release profile. Release kinetics have been found to follow either first-order kinetics or Higuchi model and release profiles in most of the cases have been found to be superior to that of conventional tablets or capsules. The present review aims to sum up the various studies on solid dispersion tablets and establish the novelty of this unique approach in the overall improvement of oral bioavailability of poorly water-soluble drugs in a simple and cost-effective manner.